Biomass Production of Nannochloropsis sp Cultivated in Combination of Vanname Shrimp Culture Wastewater and Photoperiod as Important Step of Biodiesel Production - Rachma Rusydi; Eva Ayuzar; Muliani; Munawwar Khalil; Indri Widia Wulandari; Momika Alfaini (LPPM Universitas Malikussaleh, 2022)
Nannochloropsis sp becomes one of potential microalgae which has high lipid content and be explored as biodiesel feedstock. Cultivation of Nannochloropsis sp in appropriate manner, low cost, and sustain is the main approach to provide feedstock of biodiesel effectively. By utilizing vannamei shrimp culture wastewater combined to photoperiod, the biomass production of Nannochloropsis sp can be resulted optimally. The purpose of this study was to evaluate the combination of vannamei shrimp culture wastewater and photoperiod effectiveness in biomass production of Nannochloropsis sp for supporting biodiesel production. The study used experimental laboratory as its method and Factorial Completely Randomized Design as its experimental design. Two factors of treatments namely (1) different percentage of vannamei shrimp culture wastewater and (2) different photoperiod. The levels of first factor were A: Walne, B: 50% of wastewater, C: 75% of wastewater, and D: 100% of wastewater. Then, the levels of second factor were A: 6:18 (L:D), B: 12:12 (L:D), C: 18:6 (L:D), and D: 24:0 (L:D). The result showed that the highest biomass production was achieved by combination 75% of vannamei shrimp culture wastewater and photoperiod 12:12, in amount 12.75 ± 0.212 grams/L. Statistical analysis presented that different media of wastewater and different photoperiod significantly effect on biomass production of Nannochloropsis sp (p<0.05). Interaction of those two factors also significantly effect on biomass production of that microalgae (p<0.05). The recommendation of this study was the combination of vannamei shrimp culture wastewater 75% and photoperiod 12:12 (L:D) for Nannochloropsis sp cultivation.